Rituximab in pemphigus and pemphigoid patients: Treatment outcomes and safety profile - A 6-year tertiary center study - Sivakanth Gopakumar; Nima Teresa Andrew; Maria Jose; Sanitha Kuriachan; Jumi Jacob (Asian Journal of Medical Sciences)
Background: Pemphigus and pemphigoid are autoimmune blistering disorders characterized by autoantibodies attacking skin and mucous membranes. Rituximab, targeting CD20-positive B cells, has emerged as a treatment option for resistant cases.